The effect of gluteus medius Kinesio(R) taping on torso-pelvic separation during the golf swing, ball flight distance and accuracy - Pearce, Boudine (My University, 2013)
Introduction: The effect that an increased torso-pelvic separation (x-factor) has on driving performance and accuracy is well appreciated by golfers and golf instructors. Increased torso and pelvic separation produces a greater upper trunk energy store to be utilised for a more powerful downswing. Specific muscles’ contribution towards pelvic stability during the golf swing has not been well documented. Aim: The aim of this study is to determine the effect that gluteus medius Kinesio® Taping has on torso-pelvic separation, subsequent ball flight distance and accuracy. Method: The study was a one group pre-test-post test quasi-experimental design. A group of amateur golfers underwent a biomechanical golf swing analysis with iClub™ Body Motion System to determine torso-pelvic separation at the top of the backswing. Ball flight distance and accuracy (smash factor ratio) were measured with the FlightScope®. These outcomes were recorded with and without Kinesio® Tape application on the gluteus medius muscle. Each participant’s dominant gluteus medius muscle strength was tested with a Microfet Hand-held Dynamometer before and after Kinesio® Tape application. The data gathered in the taped and non-taped groups was analysed using a paired t-test, when testing at the 0.05 level of significance. Correlation between gluteus medius and x-factor, ball flight distance and smash factor ratio with and without KT application, was done using Pearson Correlation analysis. Results: The results showed that Kinesio® Tape is effective in improving gluteus medius muscle activation and thereby the relative muscle strength (p=0.00<0.05). With regard to the other aforementioned outcome measures, x-factor, ball distance and accuracy, results showed no statistical significance (p=0.28, p=0.53 and p=0.1 respectively). Correlation analysis revealed a negative relationship between gluteus medius muscle strength and x-factor (r = -0.46, p = 0.01) and smash factor ratio (r = -0.33, p = 0.08) Discussion Kinesio® Tape has been shown to improve strength in target muscles. As the golf swing is so complex, involving the entire kinetic chain, each golfer differs significantly in his/her swing. This study showed that the gluteus medius strength improved with Kinesio® Tape application in the majority of the golfers tested, but affected each golfer’s shot differently. This highlights the fact that each golfer’s swing is unique and they utilise the kinetic chain differently. Conclusion: Kinesio® Tape is significantly effective in improving gluteus medius muscle activation and strength in amateur golfers. X-factor, ball distance and accuracy are dependent on a wide variety of body movements that act in harmony to produce the golf swing and a statistically significant result was not found regarding these outcome measures. It is thus difficult to isolate only one muscle in creating pelvic stability and only the pelvis in the motion of the golf swing.
Keywords: Muscles--physiology